Manajemen Mutu Pendidikan: Strategi Pengasuhan Mahasantri Pondok Pesantren Tahfidzul Qur’an Fatimah Az-Zahra Magetan - Rochim, Elhaq; Iman, Nurul; Rohmadi (Tahta Media Group, 2022)
Slowly a civilization that is changing, all aspects are required to follow the flow of change, including educational institutions, especially Islamic boarding schools. Like it or not, Islamic boarding schools must have a quality in the midst of the development of this era to maintain their existence in the world of education and be able to produce human resources that are relevant to the needs of the community. This study aims to find out: (1) How is the education of PPTQ students Fatimah Az-zahra. (2) How is the parenting strategy for PPTQ Fatimah Az-Zahra students (3) How is the parenting strategy for PPTQ Fatimah Az-Zahra students from the perspective of education quality management, while this study uses qualitative methods using a descriptive approach and researchers take data sources from primary data, namely the main data which will be processed and analyzed sourced from observations and direct interviews with related parties, secondary data or complementary data in the form of documentation. As for the results of the research (1) education at PPTQ Fatimah Az-zahra there is academic and non-academic education where the academic curriculum uses the Indonesian Dakwah Council curriculum equivalent to education in Dirosah Islamiyah (D2) and non-academic in the form of a tahfidz diploma. (2) The parenting strategy is carried out in collaboration with the recitation assembly in Magetan and monitoring by conducting evaluations every week, month and year (3) Implementation of the parenting strategy for students from the perspective of education quality management at PPTQ Fatimah Az-zahra using planning, oraginizing , actuacting, controlling (POAC).